The Urgency of New Renewable Energy Regulation as an Efficiency in The Utilization of Natural Resources in Indonesia - Pelengkahu, Muhammad Rahjay; Najicha, Fatma Ulfatun; Karjoko, Lego (Universitas Pendidikan Nasional, 2024)
Natural resources are utilized and controlled to achieve the well-being and prosperity of the population, as directed by Article 33 paragraph (3) of the 1945 Constitution. The state is responsible for designing policies to mitigate the ecological crises and environmental deterioration caused by the usage of natural resources, particularly energy, to prevent ecological disasters. Utilizing New Renewable Energy can help mitigate environmental harm, optimize natural resource potential, and promote community well-being. This research intends to investigate the necessity of controlling the utilization of natural resources, particularly focusing on new and renewable energy (EBT) as a key strategy to optimize the use of natural resources in Indonesia. This study is prescriptive juridical-normative legal research. The legal materials utilized consist of primary and secondary legal materials obtained through library research. The legal materials are evaluated using a logical syllogism tool. The research findings indicate that the advancement of EBT in Indonesia would not only affect the economy but also provide advantages to the society. Using EBT will enhance efficiency and promote the attainment of a pristine and healthy environment. The current EBT restrictions are inadequate to support the ongoing use of EBT due to its dispersion across many laws and regulations. The Government must align and coordinate laws and regulations in the energy sector to prevent any duplication of legislation within the legal framework. Creating a specific law for EBT will help address the legal gaps in the EBT sector, ensuring legal clarity, protection for enterprises involved in procurement, use, and development, as well as promoting sustainable and responsible administration of EBT. Furthermore, under a specific EBT regulation, individuals might face criminal penalties for causing harm to technical facilities or equipment powered by EBT.